Time Domain Analysis of a Synchronous Generator in Distorted Power Systems - Ladjavardi, Marjan; Masoum, Mohammed; Islam, Syed (Engineers Australia, 2009)
Calculating the synchronous generator steady state operating conditions and load angle is essential for power system studies. Time and space harmonics can cause variations on power system operation. This paper investigates the impact of time and space harmonics on the synchronous generator inductances, rotor currents, produced stator fl uxes and voltages, electromagnetic torque, and the steady state rotor angle. Harmonic domain and abc-frame of reference is used for non-linear modelling of synchronous generators. The instantaneous electromagnetic torque is calculated using rotational voltage component. Simulation results show that the presence of harmonics can affect the synchronous generator steady state operation and damper windings have considerable impact on the produces stator fluxes and voltages in the presence of harmonics. MATLAB/Simulink software and Simpower system toolbox are used for the simulation in time domain.